Crystal structure of ethyl 1′, 1′′-dimethyl-2′′, 3-dioxo-3H-dispiro[benzo[b]thiophene-2, 3′-pyrrolidine-2′, 3′′-indoline]-4′-carboxylate. (March 2015) - Savithri, M. P.; Suresh, M.; Raghunathan, R.; Raja, R.; SubbiahPandi, A.
No abstract available